2012
DOI: 10.1371/journal.pone.0041359
|View full text |Cite|
|
Sign up to set email alerts
|

Structure of an MmyB-Like Regulator from C. aurantiacus, Member of a New Transcription Factor Family Linked to Antibiotic Metabolism in Actinomycetes

Abstract: Actinomycetes are important bacterial sources of antibiotics and other secondary metabolites. Many antibiotic gene clusters are controlled by pathway-specific activators that act in response to growth conditions. Here we present the crystal structure of an MmyB-like transcription regulator MltR (PDB code 3pxp) (Caur_2278) from Chloroflexus aurantiacus, in complex with a fatty acid (myristic acid). MltR is a distant homolog of the methylenomycin activator MmyB and consists of an Xre-type N-terminal DNA-binding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 51 publications
1
13
0
Order By: Relevance
“…The regulatory cascade is complicated by the presence of genes for two ArpA-like proteins (60). The crystal structure of an MmyBlike protein from a thermophilic Gram-negative organism (purified from an Escherichia coli expression system) revealed that its PAS domain was complexed with a saturated fatty acid, prompting speculation that binding of a fatty acid ligand might be required to confer transcription factor activity on MmyB (61). MmyB paralogues are widespread among actinomycetes and particularly among streptomycetes.…”
Section: Cascade Regulation Of Methylenomycin Biosynthesismentioning
confidence: 99%
See 1 more Smart Citation
“…The regulatory cascade is complicated by the presence of genes for two ArpA-like proteins (60). The crystal structure of an MmyBlike protein from a thermophilic Gram-negative organism (purified from an Escherichia coli expression system) revealed that its PAS domain was complexed with a saturated fatty acid, prompting speculation that binding of a fatty acid ligand might be required to confer transcription factor activity on MmyB (61). MmyB paralogues are widespread among actinomycetes and particularly among streptomycetes.…”
Section: Cascade Regulation Of Methylenomycin Biosynthesismentioning
confidence: 99%
“…About half of them are located very close to genes with homologues in secondary metabolism, and the others are next to diverging genes for medium-or short-chain alcohol dehydrogenases. Only one of the paralogues, SCO4944, is widely conserved in other streptomycetes, and in S. griseus this gene is just one gene away from the biosynthetic gene for A-factor and is regulated by A-factor (61). Thus, MmyB-like proteins may be closely associated with secondary metabolism and fatty acid metabolism.…”
Section: Cascade Regulation Of Methylenomycin Biosynthesismentioning
confidence: 99%
“…This domain is often fused with other various domains to allow highly diverged physiological functions, such as phage repression (McDonnell and McConnell, 1994), modulation of restriction-modification systems (McGeehan et al, 2008), swarming motility and biofilm formation (Wang et al, 2014), virulence (McCallum et al, 2010) and anaerobic catabolism (Barrag an et al, 2005). A globular structure formed by five ahelices is a common feature of the XRE-type DNA binding domain (Xu et al, 2012). The XRE-type domain forms a dimer to recognize a pseudo-dyad sequence such as GACT-AGTC (McGeehan et al, 2008).…”
Section: Conservation Of a Cis-acting Element And Recognition By Cnfrmentioning
confidence: 99%
“…Members of the XRE family are involved in a wide range of gene regulation activities, including plasmid copying, restriction and modification systems, bacteriophage transcription control, and stress responses [36]. One typical class of XRE is the MmyB family, which comprises transcriptional factors with many homologs, is found predominantly in actinobacteria, and whose members are thought to play important roles in secondary-metabolite and fatty-acid metabolism [37]. The LuxR family is primarily involved in quorum sensing, biosynthesis, and metabolism, and the MerR family, which functions in detoxification and resistance, is mainly triggered by heavy metals, antibiotics, and oxidative stress [36], [38].…”
Section: Resultsmentioning
confidence: 99%